Institutionalizing Religious Habituation Through Lecture SOPs: A Qualitative Study of Student Character Formation - Laily Farihatul Izza; Eva Fauziah; Novita Dwi Astuti; Enda Tomia; Ain Fahiyana (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
This study aims to examine the institutionalization of religious habituation through lecture Standard Operating Procedures (SOPs) as a strategy for student character formation. The religious habituation analyzed includes tawasul, the recitation of Sholawat Fatih, the reading of institutional and study program vision and mission statements, and the reading of financial principles, which are routinely conducted before lectures begin. This research employs a qualitative approach with a descriptive-analytical design. Data were collected through observation, in-depth interviews, and document analysis involving institutional leaders, lecturers, and students as key informants. Data analysis was conducted interactively through data reduction, data display, and conclusion drawing. The findings indicate that religious habituation institutionalized through lecture SOPs contributes significantly to the development of student character, particularly in strengthening religiosity, discipline, academic responsibility, humility (tawadhu’), social solidarity, and learning motivation. Moreover, this practice fosters a religious, conducive, and worship-oriented academic atmosphere, positioning learning activities not merely as academic obligations but also as acts of devotion to Allah SWT. The study concludes that structured and policy-based religious habituation serves as an effective instrument for internalizing Qur’anic values and reinforcing academic culture in Islamic higher education institutions